Enhancing supervision efficiency and satisfaction: Evaluating the impact of the e-monprakerin model on vocational high school apprenticeship monitoring - Sutikno, Sutikno (Universitas Negeri Padang, 2024)
This study presents a novel approach to addressing the challenges brought about by Industry 4.0 in vocational education, particularly within the context of Indonesia's evolving industrial landscape. With industries increasingly embracing digitalization and automation, traditional apprenticeship supervision methods have struggled to keep pace. In response, this research introduces the e-monPrakerin model, an electronic-based supervision system tailored for vocational high schools (Bahasa: Sekolah Menengah Kejuruan/SMK). Through rigorous evaluation employing a randomized control group pretest-posttest design, the study demonstrates the effectiveness of the e-monPrakerin model compared to conventional methods. Results reveal significant improvements in practicality and user satisfaction, with practicability scores soaring from 41.1% to 81.3% and user satisfaction scores escalating from 31.6% to 84.4% post-implementation. These outcomes underscore the e-monPrakerin model's ability to optimize apprenticeship monitoring, offering a cost-effective, user-friendly, and efficient solution for navigating the complexities of Industry 4.0. By leveraging information technology to bridge the gap between vocational education and industry demands, this research sheds light on the practical implications of digital monitoring solutions. Ultimately, the e-monPrakerin model represents a substantial advancement in vocational education, showcasing the efficacy of technology-driven approaches in enhancing monitoring efficiency and user satisfaction. This contribution adds valuable insights to the field, benefiting educators, policymakers, and stakeholders alike in their efforts to equip the workforce with the skills necessary to thrive in the era of Industry 4.0.